Jovens adultos em redes: significados dos autorretratos postados no Instagram - Hage, Zakiee Castro Mufarrej (2017)
In the current technological scenario, social networks are part of the daily lives of young Brazilian adults and stimulate people's exposure. One of the main ways to expose yourself online is photographic posts. Research shows that Brazil is the second country that most accesses the Instagram application and its most connected public are young adults. In this context, the present research adopted a systemic vision and had as objective to identify the styles of use and to understand the meanings attributed by young adults to the photographs of self - portraits posted in Instagram. For this, the mixed sequential explanatory method was used, with a quantitative analysis of 60 profiles and later a qualitative phase, with semi-structured interviews with six collaborators, selected during the first phase of the research. In the quantitative phase, the application styles were identified, which pointed to the categories proposed in the literature and six other categories of images and sub-categories of self-portraits. The total hashtags posted were also counted. From a statistical analysis it was verified that the category of images most posed by men and women corresponds to the self portraits, with a large majority over the other categories: 44% and 43%, respectively. Within the subcategories of self-portraits, the face figures stand out for both sexes: 47% for men and 43% for women. Six interviewees with three men and three women were selected, based on the maximum variability criterion: two higher posters, two medium posters and two minimum posters. The interviews were analyzed through the thematic analysis and indicated that Instagram is an application that offers greater freedom of exposure, compared to other applications, with employees stating that in the application they can be shown in a less contained way, in a context of greater privacy. Participants are influenced by the external look in their posts and have been attentive to the rules of the number of photos that can be posted per day. The meanings attributed to the posts were: privacy, memory, beauty and happiness